RANCANG BANGUN ALAT BANTU DIAKNOSIS DAN SISTEM PEMANTAUAN NIRKABEL BAGI PASIEN PENDERITA DEMAM BERDARAH - , INTAN PUTRI K ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dengue hemorragic fever is a viral disease spread by mosquitoes in tropical and subtropical country.Based on data from the Indonesian Ministry of Health, during the year 2011 there are more than 60.000 people suffered from dengue hemorrhagic fever, with a mortality rate of about 1 percent of the total patients with this disease There is no specific treatment or vaccine for dengue fever patients. Available treatment includes plenty intravenous fluids and blood transfusion. Dengue fever patients had a high fever and their body is dehydrated due platelet count decreased and hematocrit increased causing blood to have condensation and the body loses a lot of fluids, nurses must regularly monitor the condition of the patient's body temperature and intravenous transfusion dose. Because if the patients are not treated properly then their condition will deteriorate. It is becoming a problem in small clinic with just a few employees because it is very difficult to manage so many hospitalized patients while nurses and doctors should frequently check the condition every patient's vital body signs from one room to another. Wireless monitoring system and diagnostic tool for dengue fever patients were made to remotely monitor health status. This system can speed up diagnosis of the disease and determine treatment for a patient according to the symptoms of the disease, able to deliver patient's condition data faster and give more efficient health care. As for the supporting components on the health monitoring system is HC-06-D bluetooth data communication module which is a low-voltage wireless transmitter, the measured parameter in this research are the body temperature of the patient and the intravenous transfusion dose. Data from temperature sensor and intravenous dose gauge received by computer in the central monitoring room, then the data is stored in a database so that the nurses and doctors able to monitor patients condition anytime. Keywords: wireless,diagnostic,dengue hemorraging fever, body temperature, intravenous transfusion doses